1997
DOI: 10.1111/j.1699-0463.1997.tb05072.x
|View full text |Cite
|
Sign up to set email alerts
|

A short exposure to a high‐glucose milieu stabilizes the acidic vacuolar apparatus of insulinoma cells in culture to ensuing oxidative stress

Abstract: U. T. A short exposure to a high-glucose milieu stabilizes the acidic vacuolar apparatus of insulinoma cells in culture to ensuing oxidative stress. APMIS 105:It was recently suggested that extracellular hydrogen peroxide, after diffusing into and throughout adjacent cellswhich may be the case if they have only a weak capacity to degrade hydrogen peroxidelabilizes their lysosomal compartment due to its content of low-molecular-weight iron in redox-active form. The iron would be present as a consequence of norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
(41 reference statements)
2
22
0
Order By: Relevance
“…The finding that exposure to two structurally unrelated metal chelators preserved lysosomal stability both under and after the steady-state oxidative stress, and prevented apoptosis as well, is consistent with our previous observations when H # O # was used in large bolus doses [3,4]. The protection by pre-exposure to desferrioxamine, which is taken up only by endocytosis and stored intralysosomally [21][22][23], confirms that lysosomal vul-…”
Section: Figure 5 Effects Of Desferrioxamine and 22h-dipyridyl On Lysupporting
confidence: 90%
See 1 more Smart Citation
“…The finding that exposure to two structurally unrelated metal chelators preserved lysosomal stability both under and after the steady-state oxidative stress, and prevented apoptosis as well, is consistent with our previous observations when H # O # was used in large bolus doses [3,4]. The protection by pre-exposure to desferrioxamine, which is taken up only by endocytosis and stored intralysosomally [21][22][23], confirms that lysosomal vul-…”
Section: Figure 5 Effects Of Desferrioxamine and 22h-dipyridyl On Lysupporting
confidence: 90%
“…Desferrioxamine is taken up into cells by endocytosis [21][22][23] and, consequently, binds lysosomal low-molecular-mass redoxactive transition metals. 2,2h-Dipyridyl is a lipophilic compound that transverses membranes freely [24] ; hence, a broader cellular range of effects may be expected with 2,2h-dipyridyl.…”
Section: Fenton Chemistry Lysosomes and Apoptosismentioning
confidence: 99%
“…However, several data have demonstrated that iron could play a crucial role in the inhibition of insulin expression in -cell (Guillygomarc'h et al, 2001;Fernández-Real, López-Bermejo, & Ricart, 2002). We therefore suggest that the DFO-induced increase in insulin expression may be mediated by iron chelation, which may also explain at least in part the reported protection against oxidative stress by Olejnicka et al (1997Olejnicka et al ( , 1999 in -cells. At the optimal concentration of 10 µmol/L DFO, an inhibition of cell apoptosis was observed with a decrease in Bax expression, a regulating protein involved in the activation of apoptosis (Messaris et al, 2004).…”
Section: Discussionmentioning
confidence: 72%
“…DFO removes both free and bound iron from hemosiderin and ferritin but not from hemoglobin, transferrin, or cytochromes. Moreover, DFO protects myocytes against peroxide-induced damages (Le et al, 1994), and by stimulating VEGF expression in cells (Agani & Semenza, 1998) it protects them against oxidative stress (Olejnicka, Ollinger, & Brunk, 1997;Olejnicka et al, 1999) and macrophagic activation (Mendola, Wright, & Lacy, 1989;Olejnicka et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that a combination of the above strategies, particularly ischemic preconditioning and enhanced VEGF expression would be beneficial. (17)(18)(19). Preconditioning with DFO stabilizes HIF-1a and protects neuronal cells against cytokine mediated cell death (20).…”
Section: Native Human Islets Reside In a Microenvironment Supplied Wimentioning
confidence: 99%